Digital affordances and entrepreneurial dynamics: New evidence from European regions. (January 2023) - Belitski, Maksim; Korosteleva, Julia; Piscitello, Lucia
Abstract: The advent of digital economy has brought about major changes, and understanding their impacts on entrepreneurial dynamics is a challenge for managers and policymakers. We adopt Richard Florida's three Ts (talent-tolerance- technology) framework for a region and evaluate how the interplay between technology and digital affordances shape regional entrepreneurial dynamics. Using data on 112 European regions in 21 countries (2008–2015) we distinguish between the role that technology and digital affordances play on new business formation, survival and high-growth employment. We find that complementarities between digital, culture and human capital affordances within the 3 T framework serve as a conduit for a net entrepreneurial entry, while the complementarities between technology and human capital affordances reduce high-growth employment. Joint negative effect of a technology and human capital affordances on high-growth employment and business survival is seen as lack of required skills in high-tech industries to facilitate technology diffusion. Our findings offer policy and managerial implications. Highlights: High-tech technology and digital affordances have a differentiated impact on entrepreneurship. Technology affordances remain confined within high-tech sectors, while the effect of digital affordances spillovers to other sectors, facilitating new entry. The effect of digital affordances is greater in complementarity with other regional affordances, such human capital and cultural affordances. Technology intensity jointly with human spatial affordances have a negative effect on survival and high-employment rates. The latter indicates lack of required skills in technology-intensive industries. Digital affordances have a job displacement effect, but it signifies a decrease in demand for labour across all range of skills as a result of digitalisation of some value-chain activities.